A wearable hemofilter for continuous ambulatory ultrafiltration - Gura, V.; Ronco, C.; Nalesso, F.; Brendolan, A.; Beizai, M.; Ezon, C.; Davenport, A.; Rambod, E. (Kidney international, 2008)
Ultrafiltration is effective for treating fluid overload, but there are no suitable machines for ambulatory treatment. This study summarizes the use of a light-weight wearable continuous ambulatory ultrafiltration device consisting of a hollow fiber hemofilter, a battery operated pulsatile pump, and two micropumps to control heparin administration and ultrafiltration. Six volume-overloaded patients underwent ultrafiltration for 6 h with treatment discontinued in one patient due to a clotted catheter. Blood flow averaged 116 ml min−1, the ultrafiltration rate ranged from 120–288 ml h−1 with about 150 mmol of sodium removed. Blood pressure, pulse, and biochemical parameters remained stable with no significant hemolysis or complications. Our data show that the wearable hemofilter appears to be safe, effective, and practical for patients. This device could have a major impact on the quality of life of fluid-overloaded patients with heart failure. Additional studies will be needed to confirm these initial promising results.